Multirater Validation of Peripapillary Hyperreflective Ovoid Mass-like Structures (PHOMS). (1st November 2020) - Petzold, Axel; Biousse, Valerie; Bursztyn, Lulu; Costello, Fiona; Crum, Alison; Digre, Kathleen; Fraser, Clare; Fraser, J. Alex; Katz, Bradley; Jurkute, Neringa; Newman, Nancy; Lautrup-Battistini, Jette; et al.
ABSTRACT: Peripapillary hyperreflective ovoid mass-like structures (PHOMS) are a new retinal optical coherence tomography (OCT) finding. The Optic Disc Drusen Studies Consortium had made recommendations to distinguish PHOMS from true optic disc drusen (ODD) in 2018. While publications on PHOMS have increased since then, the accuracy of the definition of PHOMS and reliability of detection is unknown. In this multi-rater study, we demonstrate that the 2018 definition of PHOMS resulted in a poor multi-rater kappa of 0.356. We performed a Delphi consensus process to develop a consistent and refined definition of PHOMS with clear principles around the nature of PHOMS and how they differ from normal anatomy. Fifty explanatory teaching slides, provided as supplementary material, allowed our expert group of raters to achieve a good level of agreement (kappa 0.701, 50 OCT scans, 21 raters). We recommend adopting the refined definition for PHOMS.